BEHAVIOURAL DIFFICULTIES: CHILDREN’S POINT OF VIEW - Alisauskas, Algirdas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The author aimed at analysing the satisfaction with a school and education of primary school children, having behavioural problems, as well as to disclose the character and causes of their experienced difficulties, and describe their anxieties due to inappropriate behaviour. The structured interviews with children have been applied. Children had an opportunity to add their comments to certain question. It was found that the controversial approach towards the school is common for those children who experience behavioural difficulties. In the school the need of children to communicate with their peers is satisfied, however they are not satisfied within the requirements of education as well as with the conflict relationships with other students in a school. Children feel concern about their inappropriate behaviour, and experience anxiety and tension. However, they used to blame themselves because of inappropriate behaviour at school. Teachers are not enough focused on the support to a child, but usually shifts the responsibility on him or her.